The effect of adverse and positive experiences on inflammatory markers in Australian and UK children - Priest Naomi; Guo Shuaijun; Gondek Dawid; Lacey Rebecca E; Burgner David; Downes Marnie; Slopen Natalie; Goldfeld Sharon; Moreno-Betancur Margarita; Kerr Jessica A; Cahill Stephanie; Wake Melissa; et al. (Elsevier Inc., 2025)
BACKGROUND
The relationship between childhood adversity and inflammation is well-established. Examination of positive experiences can provide a more complete understanding of intervention opportunities. We investigated associations of adverse and positive experiences, and their intersection, with inﬂammation in children and adolescents.
METHODS
Data sources: Longitudinal Study of Australian Children (LSAC; N = 1237) and Avon Longitudinal Study of Parents and Children (ALSPAC; N = 3488). Exposures: Adverse and positive experiences assessed repeatedly (LSAC: 0-11 years; ALSPAC: 0-15 years). Outcomes: Inﬂammation quantiﬁed by high sensitivity C-reactive protein (hsCRP) and glycoprotein acetyls (GlycA) (LSAC: 11-12 years; ALSPAC: 15.5 years). Analyses: Linear regression on the log-transformed outcomes estimated the relative difference in inﬂammatory markers with adverse/positive experiences, adjusting for socio-demographics and concurrent positive/adverse experiences, respectively.
RESULTS
Most associations were in the expected direction but differed in magnitude by exposure, outcome and cohort. Across both cohorts, adverse experiences were associated with up to 7.3% higher hsCRP (95% CI: -18.6%, 33.2%) and up to 2.0% higher GlycA (95% CI: 0.5%, 3.5%); while positive experiences were associated with up to 22.1% lower hsCRP (95% CI: -49.0%, 4.7%) and 1.3% lower GlycA (95% CI: -2.7%, 0.2%). In LSAC, the beneficial effect of positive experiences on inflammation was more pronounced among those with fewer concurrent adverse experiences.
CONCLUSION
Across two cohorts, we found small but directionally consistent associations between adverse experiences and higher inflammation, and positive experiences and lower inflammation, particularly for GlycA. Future research should give further consideration to positive experiences to complement the current focus on adversity and inform the design and evaluation of early life interventions.